Analysis of steady-state characteristics for a newly designed high voltage gain switched inductor Z-source inverter - Subhani, N. (MDPI AG, 2019)
This paper aims to develop a new switched inductor assisted strong boost Z-source inverter (SL-SBZSI) topology with high voltage gain and analyze the steady-state characteristics of the proposed topology. In the proposed topology, two switched inductors are used within the series impedance structure of the Z-source inverter (ZSI) in order to achieve the high voltage gain. The steady-state characteristics of the proposed topology are analyzed to disseminate its several advantages as compared to traditional ZSIs. The key advantages include the higher boost factor with lower shoot-through duty ratio and lower voltage stresses on capacitors as well as on switches of the inverter bridge. Furthermore, the proposed topology has the soft-start ability which significantly reduces the inrush start-up current while comparing with the traditional ZSI. In the proposed topology, a common ground is shared between the output AC voltage and the input DC voltage source which categorizes this topology to the doubly grounded inverter. The characteristics of the proposed SL-SBZSI are analyzed by considering two operating condition where the simple boost pulse width modulation (PWM) scheme is used to extract the shoot-through pulses. The characteristics of the proposed topology are also compared with different existing topologies along with the conventional modified capacitor assisted Z-source inverter (MCA-ZSI), whose boost factor is much closer to the proposed topology. Rigorous mathematical analyses are presented to clearly demonstrate the benefits of the proposed topology while simulation studies are carried out to demonstrate its distinct features as compared to the existing topology. Finally, experimental studies are conducted to further validate the theoretical and simulation results. Â© 2019 by the authors. Licensee MDPI, Basel, Switzerland.